Relationship between Implant Contraceptive Use and Acceptor Body Weight Changes - Eka Jarmiati; Sunanto; Iis Hanifah (KHD Production, 2023)
Family planning is one of the most effective ways to increase family resilience, health, and safety for mothers, children, and women. This study aimed to analyze the relationship between implant contraceptive use and acceptor weight changes. The research design in research is correlational analytic research. The population in this study were mothers who used implant contraception in the working area of ​​Pustu Blado Kulon, Probolinggo Regency, in January 2022, with as many as 69 people. The number of samples is 69 people with a total sampling technique. Collecting data using a questionnaire, then the data is processed using SPSS using chi-square. In body weight, implant changes acceptor's weight obtained a p-value of 0.015 (smaller than a=0.05) so there is a significant relationship between the variable use of implants and changes in body weight in acceptors. maternal weight gain while using hormonal contraceptives between 1-2 kg at the start of using contraceptives. This weight gain is still considered normal because weight gain is caused by fluid retention, increased body fat, and increased appetite. Attention is needed if the acceptor's weight gain exceeds 2 kg while using hormonal contraception.